The Impact of Marzano's Instructional Strategies on Grade 10 Students' Achievement in Reading Comprehension in the United Arab Emirates - MUSMAR, RAMIA DIRAR SHEHADEH (2019)
This study, an investigation of the impact of using Marzano’s instructional strategies to teach reading comprehension in a second language (L2), focuses on secondary students in the United Arab Emirates (UAE). Learning English as the official L2 has developed to be a necessity for students in the UAE, where many are alarmingly classified as underperforming. Based on the unsatisfying academic performance in literacy skills in international exams, it is anticipated that critical achievement gaps between reform endeavors and students' performance continue to exist and it appears challenging to close these gaps without practical and meaningful implications of the pillars of effective pedagogy. To lead the transformation and improve its trajectory, the Ministry of Education (MoE) in the UAE has devoted considerable attention to enhance students’ achievement, support teachers to use Marzano’s instructional strategies and adopt these strategies for formal observations in the teachers' performance appraisal system. Thus, the purpose of this study was to investigate the impact of Marzano's instructional strategies on grade 10 students' achievement in reading comprehension. It also aimed at exploring the perceptions of those students towards using Marzano’s strategies in their learning of reading comprehension strategies. Research questions for this study employed an explanatory sequential mixed methods design, involving a quasi-experimental non-equivalent pre-test–post-test control group design (n= 480 students) and focus group interviews (n=12 students). To ensure that the participants who undertook the tests were statistically representative, a sampling protocol that reflected two perspectives, namely professional development training for teachers on Marzano’s strategies and a classroom observational tool for these teachers, was followed. The findings of the study, which indicated significant differences in tests scores (F =15.125; P =0.0) and students’ positive perceptions towards using the strategies, demonstrate the importance of Marzano’s instructional strategies on enhancing students’ achievement in reading comprehension. Results also showed that female students significantly outperformed male students in posttests. It is hoped that this study will fill the actual knowledge gap in the UAE research literature, facilitate enhanced performance for the educational field partners; students, teachers, policy makers and curriculum developers and prompt further explorations in the field of using Marzano’s instructional strategies in literacy skills instruction.